"Privilegia episcopii Cremonensis". Il cartulario vescovile di Cremona e il vescovo Sicardo (1185-1215) - Leoni, Valeria (Scrineum, 2013)
The essay examines the Codex Sicardi, one of the few episcopal chartularies composed in medieval Italy and made in the early thirteenth century according to the will of Bishop Sicard of Cremona (1185-1215), a man with a deep knowledge of legal culture, who promoted the study in his home town and who was in relationship with the Swabian Emperors and Pope Innocent III. The analysis of the book, its composition, methods of selection of documentary material for the purpose of being copied shows that Codex Sicardi differs from other episcopal chartularies (such as those of Genoa, Trento and Fermo) not only for the accurate execution, but also for the reasons that led to its composition: imperial and papal privilegia, placita, chartae are selected and copied to illustrate the iura of the bishopric of Cremona, especially in the field of jurisdiction, rather than its economic interests and its administrative activities.